Distribusi Ferrite dan Sifat Ketangguhan pada AISI 1020 Akibat Pengaruh Media Quenching - Halimi, Ahmad Dzulfikri; M. W. Arif Sektiono; D. Setiawan; M. Ahsin Fahmi (Universitas Nusa Putra, 2024)
This research aims to determine the toughness properties and microstructure of AISI 1020 steel material which was previously treated by using a variety of cooling media including air cooling, oil cooling and grease cooling. After being cooled by using several cooling media, it was continued with impact and microstructure testing. The results showed that AISI 1020 steel specimens using air cooling media, had the average impact strength value of 19.1 joules/mm, while those using oil cooling media had an average impact strength of 35.2 joules/mm, and those using grease cooling media had an impact strength of 45 joules/mm. From this data, the one with the highest impact strength value was the grease cooling media at 45 joules/mm and the one with the lowest impact strength was the air cooling media, namely 19.1 joules/mm. The results of metallographic observations were obtained when the grease media was used, the distribution of ferrite was reduced and did not have time to form, whereas in steel that was cooled with oil, the distribution of ferrite was almost the same as the untreated material and for air media, the shape of the ferrite structure spread and formed evenly.